Nutrient Metabolisability of Treated False Yam (Icacina Oliviformis) Seed meal for Broiler Chickens (Ghana Journal of Science, Technology and Development, 2021)
A study was conducted to evaluate apparent metabolizable energy (AME) and nutrient metabolisability (NM) of maize-based diets containing treated false yam seed meal (TFYSM) using a 5x6 factorial [5 treatment samples (Un_T, Urea_T, NaCl_T, NaOH_T and KOH_T) at 6 levels (0, 10, 20, 30, 40 and 50) each] design for 15 days. Matured false yam (Icacina oliviformis) fruits were harvested and seeds extracted. Five different FYSM samples were prepared. One untreated sample (Un_T) was prepared by crushing fresh false yam seed and sun-drying to 12% moisture. Four treated samples (T) were crushed and each soaked in water (1:2; w/v) for 12 days with water replaced every 3 days. Afterwards, each sample was re-soaked in 1 M concentration of urea (Urea_T), sodium chloride (NaCl_T), sodium hydroxide (NaOH_T) or potassium hydroxide (KOH_T), for 24 h, washed, blanched and sun-dried to a moisture content of 12%. Apparent metabolizable energy (AME) of the experimental diets indicated an increasing trend of AME values as the level of FYSM samples were increased in the diets. Generally, all the treatment diets showed a higher AME content. However, among the treatment diets, urea, potassium hydroxide and sodium hydroxide-treated FYSM-based diets out-performed their sodium chloride treated counterpart (P0.05) the coefficients of metabolisability of dry matter (DM) and crude protein (CP). However, in terms of methods of processing, DM metabolisability was significantly higher (P